Biocomponent-based microalgal transformations into biofuels during the pretreatment and fermentation process. (April 2020) - Ha, Geon-Soo; El-Dalatony, Marwa M.; Kim, Do-Hyeon; Salama, El-Sayed; Kurade, Mayur B.; Roh, Hyun-Seog; El-Fatah Abomohra, Abd; Jeon, Byong-Hun
Graphical abstract: Highlights: Algal biocomponents has an influence on pretreatment and fermentation efficiency. Highest biofuels yield (0.44–0.55 g/g) was obtained from Pseudochlorella sp. Cell wall thickness dependent on bioconstituents and affected biofuels yield. Highest total energy recovery (42%) was achieved using suitable Pseudochlorella sp. Abstract: Microalgal cell wall integrity and composition have a significant impact on the fermentation process and biofuel recovery. In this study, various biofuels (bioethanol, higher alcohols (C3-C5), and biodiesel) were produced by the fermentation of carbohydrates and proteins, and transesterification of lipids from three different microalgal strains ( Pseudochlorella sp., Chlamydomonas mexicana, and Chlamydomonas pitschmannii ), each possessing different proportions of bioconstituents (carbohydrates, proteins, and lipids). Changes in the cell wall structure and thickness were observed before and after fermentation using transmission electron microscopy. Pseudochlorella sp. showed the highest yields of bioethanol (0.45 g-ethanol/g-carbohydrates), higher alcohols (0.44 g-higher alcohols/g-proteins), and biodiesel (0.55 g-biodiesel/g-lipids), which consequently revealed a maximum energy recovery (42%) from whole constituents. This study suggests that different physiological properties, including cell wall thickness and the proportion of bioconstituents in microalgae, could have a significant impact on the pretreatment and fermentation efficiencies for biofuels production.